‘People are Trapped in History and History is Trapped Inside Them’: exploring Britain’s Racialized Colonial Legacies in Criminological Research - Parmar, Alpa (The British journal of criminology, 2023)
In this paper, we advocate identifying the colonizing logics of race in criminological analysis, in recognition of their enduring postcolonial presence in societies like the United Kingdom. Our argument unfolds through the life stories narrated by three men entangled by colonial remnants of power(lessness), subservience, and criminalization. For Cairo (black) and Rafan (Asian), their subalternity is exposed through their vulnerability to racialized stereotypes which have a foundation in colonial histories. Both young minority ethnic men are also situated in a transnational, glocalized frame in which their racialized and gendered identities prescribed the nature of their belonging to a British nation-state irrevocably connected to the Empire. Our reflections on a third narrative interview of Barry reveal the dividends of whiteness, simultaneously occluded, disavowed, and yet wilfully upheld, but in a competitive and exclusive form of belonging. In the articulation and analysis of these stories of crime and order, we mine styles of reasoning from postcolonial theory, sociology, history, and philosophy to embolden a postcolonial criminology.